A Mini-Review on Critical Factors in Determining Angle of Pull (AOP) and Assessment Tools in Physiotherapy - Ahmad Syazwan Ahmad Kamal; Lim Zhen Hong; Rabiatul Adawiah Abdul Rahman; Bahman Jamaluddin; Rudi Setiawan; Syamimi Shamsuddin (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
The Angle of Pull (AOP) is an essential concept in physiotherapy since it determines the efficiency of rehabilitation exercises by ensuring targeted muscle engagement and optimal force application. Therefore, precise quantification of AOP as well as identification of Range of Motion (ROM) and resistance points is critical when establishing appropriate rehabilitation strategies. However, traditional methods like the universal goniometer are most used but there are certain limitations such as the parallax error and inter-rater variability which can impact the precision required in clinical settings. This mini review examines the foundational elements of ROM, baseline muscle strength, and the resistor point in determining AOP. It also assesses the strength and weakness of the available tools, like the digital HALO goniometer and the AnglePro which is the goniometer that also has laser pointer for identifying the point of resistance. Despite technological advancements, current devices still exhibit significant limitations such as high costs, dependency on traditional goniometers, and lack of comprehensive functionality. The review points out the need for a new precise device that could capture the ROM, AOP and identify specific resistance points as effectively as a digital device but at a lower cost. Such innovations would facilitate the efficiency, accuracy and effectiveness of physiotherapy practice to improve patient results. Moreover, further exploration in this area is needed to eliminate the current shortcomings and develop the above strategies.